Children's literature is a key tool in the reading process - Pacheco Tarazona, Isabel Cristina; Delgado Ayala, Paola Fernanda; Rodríguez Orduz, Zahira Milena; Leal Oviedo, Olga Ines (Rastros Rostros, 2023)
Theorists have pointed out that early reading experiences, those in which children learn to interact with fear and with their peers, constitute one of the most important processes for their integral development.
Keywords: literature; children; reading; process